Register Dynamics in the EFL Classroom: Investigating Teachers’ Language Styles in Indonesian Vocational School - Aditya Sahrul Akbar; Hanandyo Dardjito; Estri Oktarena Ikrarini (Script Journal: Journal of Linguistics and English Teaching, 2026)
Background: Style plays an important role in fostering productive interactions between teachers and students when learning English as a foreign language (EFL). Using the right style can improve information delivery and allow for the creation of a positive classroom environment. Three of Martin Joos' Five Clocks Theory: formal, consultative, and informal, are considered the most relevant in the context of Education. The findings are significant in helping teachers in vocational schools adjust their language style to enhance student communication and comprehension. Methodology: This study applied a descriptive qualitative approach with a purposive sampling technique. Seven English teachers from one of the vocational schools in Yogyakarta became respondents for the questionnaire, and two other teachers were interviewed for in-depth data. The data were analyzed using the Miles & Huberman model, which includes data reduction, data presentation, and conclusion. Findings: The questionnaire results showed that the consultative register, the formal, and the casual were the most to least used, respectively. In-depth interviews revealed that teachers adjusted their language style based on the context of delivering the material and the relational closeness with students. The formal register functions to deliver structurally complex material, while the casual register is used to build closer relationships with students. Conclusion: The use of registers helps improve learning outcomes by enabling teachers to deliver material accurately while building rapport with students, resulting in a more interactive learning environment, increased motivation, and a deeper understanding of the learning material. Combining formality and closeness through consultative and casual registers is an important strategy for teachers in adjusting their teaching approaches. Originality: This study contributes to the theory of communicative language teaching in which registers used by EFL teachers emphasize the meaningfulness of language. This study also contributes to classroom communicative theory by highlighting how teachers and students communicate to enhance students' engagement, social dynamics, and learning outcomes.